1996
DOI: 10.7326/0003-4819-125-8-199610150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fibrinogen with Glycemic Control and Albumin Excretion Rate in Patients with Non-Insulin-Dependent Diabetes Mellitus

Abstract: Patients with non-insulin-dependent diabetes mellitus had a high prevalence of hyperfibrinogenemia. Fibrinogen level was independently associated with hemoglobin A1c value and albumin excretion rate, which suggests that fibrinogen may be involved in the increased cardiovascular risk of patients with diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 0 publications
7
61
2
Order By: Relevance
“…The present study adds to this information, showing that a further increase not only of fibrinogen concentration but also of its synthesis occurs when type 2 diabetes patients are also albuminuric (Table 1) [7,8]. The slightly higher rate of fibrinogen absolute synthesis rate in the macro-vs the microalbuminuric patients may indicate some sort of consumptive coagulopathy or an increased rate of disappearance of fibrinogen in the former.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The present study adds to this information, showing that a further increase not only of fibrinogen concentration but also of its synthesis occurs when type 2 diabetes patients are also albuminuric (Table 1) [7,8]. The slightly higher rate of fibrinogen absolute synthesis rate in the macro-vs the microalbuminuric patients may indicate some sort of consumptive coagulopathy or an increased rate of disappearance of fibrinogen in the former.…”
Section: Discussionsupporting
confidence: 51%
“…It increases cardiovascular risk in type 2 diabetes mellitus [30,31], probably because it reflects widespread increased vascular permeability causing organ damage [28,31,32]. Albuminuria and hyperfibrinogenaemia, another cardiovascular risk factor, are frequently associated [7,8] in diabetes. Such an association is important in that fibrinogen, an acutephase protein, is a powerful and independent cardiovascular risk factor [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It modifies foam cell formation and several inflammatory products, contributing to the onset of atherosclerosis [31]. Fibrinogen, which is correlated with glycosylated haemoglobin and microalbuminuria [32], is known as an acute phase reactant. Increased levels of sVCAM-1, which mediates the adhesion and transmigration of leucocytes to the vascular endothelial wall, are associated with an increased risk of cardiovascular mortality in Type 2 diabetes [33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that formation of an occlusive thrombus, on a damaged atherosclerotic lesion is the most common precipitating factor of acute myocardial infarction. Evidence also suggests that fibrinogen has a role, both in the early stages of plaque formation and late complications of cardiovascular disease [2]. The excess cardiovascular morbidity and mortality among diabetics have not been fully explained by major risk factors such as hypertension, cigarette smoking and hypercholesterolemia.…”
Section: Introductionmentioning
confidence: 99%